Inferring population dynamic trends of Nothofagus pumilio and N. betuloides in coastal and mountain forests of Tierra del Fuego: contrasting from flowering to seedling survival through several reproductive cycles - Toro-Manriquez, Monica D. R.; Soler, Rosina; Huertas Herrera, Alejandro; Vanessa Lencinas, Maria; Promis, Alvaro; Blazina, Ana Paula; Martinez Pastur, Guillermo (My University, 2022)
Key message Flower to fruits x and seed-to-seedling were the most critical transition in the early regeneration cycle of pure and mixed Nothofagus forests, both in coastal and mountain geographic locations. Within mixed forest, the deciduous N. pumilio shows better recruitment performance (e.g., highest transition probabilities) than the evergreen N. betuloides. The evergreen species fails to recruit in the mixed coastal forests for two of the three analysed cohorts, which implies an advantage of N. pumilio over N. betuloides that must be further examined. However, N. betuloides in average value had a higher probability of reaching 2-year survivor in mixed forest. Transition from flower to seedling encompasses major processes that define the success of the tree regeneration, and consequently, its study is crucial in the context of forest management. Here, we analysed the transition probability of the reproductive cycle of two Nothofagus species, which formed pure and mixed forests in coastal and mountain geographic locations of Tierra del Fuego (Argentina). Pure deciduous N. pumilio (Np), pure evergreen N. betuloides (Nb), and mixed N. pumilio-N. betuloides (M) forests in coasts and mountains (3 forest types x 2 geographic locations x 20 replicas = 120 replicas) were evaluated. Reproductive structures (female flowers, fruits, seeds, sound seeds, emerged seedlings and surviving seedlings up to 2 years) were studied since 2012-2018. Our results suggested that transition probabilities from flower to surviving seedlings varied inter-annually between N. pumilio and N. betuloides. The hazard ratio in the transition showed an influence of the cohorts and the geographic location on N. pumilio, while forest type and geographic location influenced on N. betuloides. Flower to fruits and seed to seedling were the most critical process in all forest types and locations. Cumulative transition probabilities (female flowers to 2-year-old seedlings) for N. pumilio were 0.3-46.2% in Np and 1.4-30.2% in M, and pure and mixed forests reached similar probabilities only in cohort 3. For N. betuloides, these were 2.8-24.4% in Nb and 0.0-6.5% in M. Both Nothofagus species showed a better performance of pure forests in mountains (15.9-46.2% Np; 3.8-24.8% Nb) than in coasts (0.3-16.1% Np; 2.8-5.3% Nb). Through this integrated approach, considering the full reproductive cycle, it is possible to quantify the influence of canopy composition and inter-annual variability in natural forest dynamic, and allows to identify the critical stages of tree recruitment in pure and mixed Nothofagus forests.
Keywords: transition probability; reproductive phenology; seed production; pure forests; mixed forests; southern patagonia